2022
DOI: 10.3389/fphar.2022.827782
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization, Structural Characterization, and Anti-Hepatoma Activity of Acidic Polysaccharides From Scutellaria barbata D. Don

Abstract: The Chinese medicinal herb Scutellaria barbata D. Don has antitumour effects and is used to treat liver cancer in the clinic. S. barbata polysaccharide (SBP), one of the main active components extracted from S. barbata D. Don, exhibits antitumour activity. However, there is still a lack of research on the extraction optimization, structural characterization, and anti-hepatoma activity of acidic polysaccharides from S. barbata D. Don. In this study, the optimal extraction conditions for SBP were determined by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Regression analyses of the experimental data were conducted and a non-linear quadratic model was fitted using the following formula (2) [Su et al, 2022]:…”
Section: Methodsmentioning
confidence: 99%
“…Regression analyses of the experimental data were conducted and a non-linear quadratic model was fitted using the following formula (2) [Su et al, 2022]:…”
Section: Methodsmentioning
confidence: 99%
“…Scutellaria barbata polysaccharides (SBP) disrupt the cell cycle at the G0/G1 phase by downregulating the expression levels of CyclinD1 and CDK4 in H22 tumor cells. Additionally, they upregulate the expression levels of p53 and Bax/Bcl-2, thereby inducing apoptosis in H22 tumor cells [ 130 ]. In vivo and in vitro studies have demonstrated that the flavonoid compound wogonin induces the degradation of cell cycle protein D1 by activating glycogen synthase kinase-3 beta (GSK3β), effectively blocking the cell cycle in H22 tumor cells [ 59 ].…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%